Chameleon Reactivity of the Allene Bond of 4-Vinylidene-2-oxazolidinone: Novel Through-Space Conjugative Nucleophilic Addition of Electron-Rich Alkenes and Hetero-Nucleophiles - Kimura, Masanari; Horino, Yoshikazu; Mori, Masahiko; Tamaru, Yoshinao (Chemistry : a European journal, 2007)
The CαCβ double bond of allene carbamates 1 serves as an electron acceptor similar to the double bond of conjugated enones by means of a through‐space interaction with the NSO2 bond; the carbamate double bond is thus subject to nucleophilic addition for a wide variety of nucleophiles, which proceeds under mild conditions by heating at 70–100 °C. Depending on the kind of nucleophiles, 1 displays three different reaction modes: 1) Typically enol ethers and allylsilanes promote 1,3‐sulfonyl migration of 1 and undergo the inverse electron demand Diels–Alder reaction with the 1‐aza‐1,3‐butadiene intermediates II thus formed to furnish bicyclic 2‐alkoxy‐5‐sulfonyltetrahydropyridines 2 and 2‐silylmethyl‐5‐sulfonyltetrahydropyridines 3, respectively, with high regio‐ and stereoselectivity and retention of configuration of the double bonds of these electron‐rich alkenes; 2) silanes (RnSiH4−n, n=1–3) and thiols deliver the hydride and the thiolate at the Cβ carbon and promote the 1,3‐sulfonyl migration, followed by protonation of the thus‐formed carbamate anion (Z)‐III to provide, for example, (Z)‐4 a and (Z)‐4 j, respectively; 3) alcohols simply add to the CαCβ double bond and provide (E)‐6. Usually, the reaction with alcohols is accompanied by the second pathway, giving rise to, for example, (Z)‐4 b in addition to (E)‐6 b. Phenol engages in the third pathway and provides (E)‐6 g exclusively. Heteroaromatics, such as furans and benzofurans follow the first pathway, however, in a different regioselectivity from enol ethers and allylsilanes, delivering the oxygen atom at the 3‐position of 5‐sulfonyltetrahydropyridines (2 g and 2 h). Indoles, on the other hand, show a dichotomy, equally enjoying the first and the third pathways and provide mixtures of (E)‐7 and (E)‐8, respectively. Through‐space conjugative attack by neutral C‐, O‐, and S‐nucleophiles upon Cβ (see scheme) causes NSO2 bond cleavage of 1 and sulfonyl group migration from N to Cα to generate 3‐sulfonyl‐1‐aza‐1,3‐butadiene, a reactive 4π‐component intermediate for the inverse electron demand Diels–Alder reaction.